Identification of TRP-Related Subtypes, Development of a Prognostic Model, and Characterization of Tumor Microenvironment Infiltration in Lung Adenocarcinoma - Sun, Sibo; Wang, Yu; Li, Min; Wu, Jianqing (Frontiers in Molecular Biosciences, 2022)
The TRP (Transient Receptor Potential) superfamily, as cation channels, is a critical chemosensor for potentially harmful irritants. Their activation is not only closely related to tumor progression and prognosis, but also to tumor therapy response. Nevertheless, the TRP-related immune genes (TRIGs) expression of the tumor microenvironment (TME) and their associations with prognosis remain unclear. Firstly, we represented the transcriptional and genetic variations in TRIGs in 535 lung adenocarcinoma (LUAD) samples, as well as their expression patterns. LUAD samples were divided into two distinct subtypes based on the TRIGs variations. Significant differences had been found in prognosis, clinical features, and TME cell-infiltration features between the two subtypes of patients. Secondly, we framed a TRIG-score for predicting overall survival (OS) and validated the predictive capability of the TRIG-score in LUAD patients. Accordingly, to enhance the clinical applicability of TRIG-score, we developed a considerable nomogram. A low TRIG-score, characterized by increased immunity activation, indicated favorable advantages of OS compared with a high TRIG-score. Furthermore, the TRIG-score was found to have a significant connection with the TME cell-infiltration and immune checkpoints expressions. Our analysis of TRIGs in LUAD showed their potential roles in prognosis, clinical features, and tumor-immune microenvironment. These results may advance our knowledge of TRP genes in LUAD and show a new light on prognosis estimation and the improvement of immunotherapy strategies.